2004
DOI: 10.1155/2004/376572
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ion mobility spectrometry of intact viruses

Abstract: Abstract. Characterizing supramolecular interactions offers significant challenges using NMR or crystallographic techniques either because of size limitations or the difficulty in forming suitable crystals, while mass spectrometry is largely limited to low resolution mass information. Here we report gas phase measurements of intact virus particles using electrospray ion mobility spectrometry with an accuracy in radial measurements that were sufficient to differentiate closely related species. In addition, meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 25 publications
4
68
0
2
Order By: Relevance
“…ES-DMA can achieve this objective by correlating identity with size. Thomas et al, [35] has shown that the components of mixtures of very similar sized viruses can be distinguished based on size by ES-DMA.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…ES-DMA can achieve this objective by correlating identity with size. Thomas et al, [35] has shown that the components of mixtures of very similar sized viruses can be distinguished based on size by ES-DMA.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…ESI-GEMMA studies of primarily globular proteins have shown a correlation between electrophoretic diameter and relative molecular mass for proteins and protein complexes ranging from 3 kDa to 2 MDa and measuring 2.6 to 21.7 nm in EMD [8]. Highlighting the role of water in supramolecular complexes and the potential of ESI-GEMMA as a structural elucidation tool, Thomas et al showed that the measured electrophoretic mobility for selected viruses were within 15% of the diameters measured by X-ray crystallographic studies [13]. Furthermore, studies using other ESI-IMS techniques have shown agreement between X-ray crystal structure and gas-phase structure dimensions for both globular proteins and large protein complexes.…”
mentioning
confidence: 97%
“…tions [3,7,8,13]. Within the electrospray unit of the GEMMA apparatus, the protein solution is sprayed into a mist of highly charged droplets, which are then charge-reduced by a bipolar neutralizer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances have seen its successful application to systems, including the ribosome [1], intact viruses [2,3], membrane associated protein assemblies [4,5], and various protein-small molecule ligand complexes [6,7]. The use of ESI-MS to study noncovalent protein interactions offers several advantages over other biophysical techniques.…”
Section: Introductionmentioning
confidence: 99%